Digital Storytelling and Vlogging as Tools for Enhancing L2 Communication: A Mixed-Methods Study of Pakistani University Business Students (Journal of Asian Development Studies, 2025)
This study explores the impact of Digital Storytelling (DST) and video blogging (vlogging) on enhancing English language proficiency, specifically in speaking and writing, among university students in Pakistan. Despite English being the primary medium of instruction in higher education, many students struggle with fluency and writing skills, limiting their academic and professional opportunities. The research employs a mixed-methods approach, combining quantitative pre- and post-tests with qualitative interviews, to assess the effectiveness of DST and vlogging. The findings show significant improvements in both speaking and writing abilities in the experimental group, which engaged with DST and vlogging, compared to the control group using traditional learning methods. Students reported increased confidence, motivation, and engagement, with digital tools providing a more dynamic and real-world learning experience. This research underscores the potential of incorporating DST and vlogging into language curricula, particularly in Business English, to enhance communication skills. The study has significant implications for language teaching, suggesting the integration of digital tools in higher education to promote more effective and engaging learning environments.